(untitled) (Journal of human and social sciences, 2022)
This study aims to examine the incentive system and its impact on the quality of healthcare services at health centers in Tripoli, specifically at the Abu Salim Clinics Complex. These clinics were selected due to their location in a densely populated area, the high number of staff and patients compared to other health centers in Tripoli, and the range of medical and health services they provide. The complex employs approximately 290 staff members—75% medical and allied health personnel and 25% administrative staff—and serves around 100,000 cases annually (2017–2019). The Abu Salim Clinics Complex functions as a secondary healthcare facility, bridging primary health centers and major hospitals, with clinics in general medicine, pediatrics, surgery, diabetes, orthopedics, dentistry, dermatology, obstetrics and gynecology, ophthalmology, ENT, physiotherapy, radiology, and laboratory services. The study addresses the problem of low employee performance at health centers, attributed to factors such as inadequate incentive systems, insufficient training of medical and administrative staff, weak support services, and gaps in implementing and updating laws and regulations. The researchers argue that adopting a structured incentive system in health institutions positively influences job performance, thereby improving service quality and patient satisfaction. The research emphasizes the importance of material and moral incentives in motivating employees, enhancing job performance, and ensuring that organizational and personal goals are aligned. The study also considers the role of Islamic teachings in encouraging good behavior and performance through reward and recognition principles. The objectives of the study are: To assess the importance of material and moral incentives for staff at the Abu Salim Clinics Complex. To measure the impact of material incentives on employee progress and performance. To evaluate the effect of incentives on specific performance improvement elements. To identify demographic differences (gender, marital status, age, education level, experience, and job role) in staff perceptions of incentives. The study used an analytical approach with a survey instrument distributed to 80 staff members, with 60 responses analyzed. The survey included 18 items divided into three main axes to evaluate staff satisfaction and the relationship between incentives and performance. This research highlights the crucial role of incentive systems in improving the quality of healthcare services and provides insights for practical and scientific application in health administration.